Putative endogenous filovirus VP35-like protein potentially functions as an IFN antagonist but not a polymerase cofactor - Kondoh, Tatsunari; Manzoor, Rashid; Nao, Naganori; Maruyama, Junki; Furuyama, Wakako; Miyamoto, Hiroko; Shigeno, Asako; Kuroda, Makoto; Matsuno, Keita; Fujikura, Daisuke; Kajihara, Masahiro; Yoshida, Reiko; et al. (PloS one, 2017)
It has been proposed that some non-retroviral RNA virus genes are integrated into vertebrate genomes. Endogenous filovirus-like elements (EFLs) have been discovered in some mammalian genomes. However, their potential roles in ebolavirus infection are unclear. A filovirus VP35-like element (mlEFL35) is found in the little brown bat (Myotis lucifugus) genome. Putative mlEFL35-derived protein (mlEFL35p) contains nearly full-length amino acid sequences corresponding to ebolavirus VP35. Ebola virus VP35 has been shown to bind double-stranded RNA, leading to inhibition of type I interferon (IFN) production, and is also known as a viral polymerase cofactor that is essential for viral RNA transcription/replication. In this study, we transiently expressed mlEFL35p in human kidney cells and investigated its biological functions. We first found that mlEFL35p was coimmunoprecipitated with itself and ebolavirus VP35s but not with the viral nucleoprotein. Then the biological functions of mlEFL35p were analyzed by comparing it to ebolavirus VP35s. We found that the expression of mlEFL35p significantly inhibited human IFN-β promoter activity as well as VP35s. By contrast, expression of mlEFL35p did not support viral RNA transcription/replication and indeed slightly decrease the reporter gene expression in a minigenome assay. These results suggest that mlEFL35p potentially acts as an IFN antagonist but not a polymerase cofactor.